P002 WHEN THE PATIENT VOICE IS HEARD IN EDUCATION, DOES THE CLINICIAN LISTEN? DUAL TRACK PATIENT/PROVIDER EDUCATION IN IBD INCORPORATING PATIENTS AS LEARNERS AND FACULTY. (7th February 2019) - Brooks, Jacqueline; Johnson, Beth R; Clausen, David M
Abstract: Background: It is postulated that patient inclusion in planning/execution of continuing medical education (CME) activities may better engage providers, reinforce learning, and improve outcomes. RMEI Medical Education's (RMEI's) proprietary Clinical Convergence ® format, launched in 2014 and spanning 30 activities in multiple disease states, utilizes interactive case-based discussion centered on real patients to contextualize didactic learning. In the final third of the program, the patients discussed join the clinical faculty panel for a guided discussion. This series in inflammatory bowel disease (IBD) was endured and offered as a web-based educational activity, concurrent with a patient education program. This study examined the efficacy of this format on improving provider proficiency and empowering patients. Methods: The Crohn's & Colitis Foundation (Foundation) and RMEI developed a Clinical Convergence ® curriculum, comprising a series of half-day regional meetings, aimed at gastroenterology/primary care providers who manage patients with IBD; patients with IBD and their caregivers were also invited to participate in concurrent patient education. The patient/caregiver track included a workshop (led by the Foundation and faculty) focused on facilitating meaningful engagement with clinicians. Participants from both tracks then converged to discuss lessons learned. The provider track was endured online, expanding the reach to a national cohort of community clinicians. Outcomes were measured via ARS keypads (live) and web-based testing (enduring and follow-up). For patients, a composite Wellness Index measured the degree to which they felt able to actively participate in their care before and after the education. Learners' performance changes on these metrics were used to evaluate changes in proficiency. Results: 818 providers (92% physicians) participated in the four activities (61% gastroenterology providers), with N=103 completers. 102 patients participated in the live meetings. Analysis of learning objectives (Figure 1) revealed improved clinician proficiency and behavior change in key clinical areas in both live and online formats. Patients/caregivers showed improvements in knowledge regarding symptoms and treatments with commensurate improvements in confidence and intent to change ratings (Figure 2). Patients showed universal improvement across the Wellness Index. Conclusions: These findings demonstrate the applied efficacy of this program for both clinicians and patients/caregivers. Specifically, working with real patients as faculty, who are presented as case scenarios and able to discuss their perspectives on treatment, represents a unique opportunity for meaningful collaboration and conversation. It also improves professional proficiency and patient engagement.